TOPMODEL: Integrated Theory and Review - Silva, Roberto Valmir da; Kobiyama, Masato (UFPR, 2007)
The objective of the present work was to review the hydrologicalmodel TOPMODEL. This model is based on the variablesource area concept. This dynamic and distributed feature ofthe watershed is simulated with two main parameters: (1) thetopographic index that is a function of the contributing area andslope for each cell; and (2) the storage deficit that representsthe available water in the soil. Its integrated theory is describedand special attention was made to review papers that used theTOPMODEL for hydrograph forecasting, parameter sensitivityanalysis and hypotheses modification.